KARAKTERISTIK HABITAT PENELURAN PENYU DI PANTAI TAMAN KILI-KILI KABUPATEN TRENGGALEK DAN PANTAI TAMAN HADIWARNO KABUPATEN PACITAN - Arisna Aditya Pratama; Agus Romadhon (Department of Marine and Fisheries, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTTaman Kili-kili and Pelang Beaches are located in Bendogolor Village, Wonocoyo Village, Panggul Sub-district, Trenggalek District, East Java, while Taman Hadiwarno Beach is located in Hadiwarno Village, Ngadirojo Sub-district, Pacitan district, East Java. These three beaches are along the southern coastline of the island of Java. Taman Kili-kili Beach and Taman Hadiwarno Beach are beaches that are habitats for nesting of several types of sea turtles in Indonesia such as lekang turtles (Lepidochelys olivacea), hawksbill turtles (Eretmochelys imbricata) and green turtles (Chelonia mydas). This study aims to determine the quality of the waters, find out the characteristics of turtle nesting habitat and determine the inhibitory parameters of turtles to lay eggs in Taman Kili-kili Beach, Trenggalek Regency, Pelang Beach, Trenggalek Regency and Taman Hadiwarno Beach, Pacitan Regency. The method used is comparative, which compares the data obtained from the results of research with a range of existing quality standards. The results of this study are parameters of water quality in all three stations in the range of good for sea turtle habitat. Characteristics of sea turtle nesting habitats at station 1 are characterized by all parameters in the good range, at station 2 there are only 5 parameters which are in the good range and at station 3 there are 8 parameters which are in the good range for habitat sea turtle nesting. The inhibiting parameters that cause turtles not to lay eggs at station 2 are the length of the beach, sand temperature, coastal vegetation, distance of the beach with settlements and coastal atmosphere. Keywords: Taman Kili-kili Beach, Pelang Beach, Taman Hadiwarno Beach, Sea Turtle, Spawn HabitatABSTRAKPantai Taman Kili-kili dan Pantai Pelang terletak di Dusun Bendogolor, Desa Wonocoyo, Kecamatan Panggul, Kabupaten Trenggalek, Jawa Timur, sedangkan Pantai Taman Hadiwarno terletak di Desa Hadiwarno, Kecamatan Ngadirojo, Kabupaten Pacitan, Jawa Timur. Ketiga pantai ini berada di sepanjang garis pantai selatan pulau jawa. Pantai Taman Kili-kili dan Pantai Taman Hadiwarno merupakan pantai yang menjadi habitat peneluran dari beberapa jenis penyu yang ada di Indonesia seperti penyu lekang (Lepidochelys olivacea), penyu sisik (Eretmochelys imbricata) dan penyu hijau (Chelonia mydas). Penelitian ini bertujuan untuk mengetahui kualitas perairan, mengetahui karakteristik habitat peneluran penyu dan mengetahui parameter penghambat penyu untuk bertelur di Pantai Taman Kili-kili Kabupaten Trenggalek, Pantai Pelang Kabupaten Trenggalek dan Pantai Taman Hadiwarno Kabupaten Pacitan. Metode yang digunakan adalah komparasi yaitu membandingkan antara data yang di dapat dari hasil penelitian dengan kisaran baku mutu yang ada. Hasil dari penelitian ini adalah parameter kulitas perairan di ketiga stasiun berada pada kisaran baik untuk habitat penyu. Karakteristik habitat peneluran penyu di stasiun 1 dicirikan dengan seluruh parameter berada pada kisaran baik, pada stasiun 2 hanya terdapat 5 parameter yang berada pada kisaran baik dan pada stasiun 3 terdapat 8 parameter yang berada pada kisaran baik untuk habitat peneluran penyu. Parameter penghambat yang menyebabkan penyu tidak melakukan peneluran di stasiun 2 adalah panjang pantai, suhu pasir, vegetasi pantai, jarak pantai dengan pemukiman dan suasana pantai.Kata Kunci: Pantai Taman Kili-kili, Pantai Pelang, Pantai Taman Hadiwarno, Penyu, Habitat Peneluran.